Symmetry through the Eyes of a Chemist - Hargittai, Magdolna (Springer, 2017)
They are currently affiliated with the Department of Inorganic and Analytical Chemistry and Materials Structure and Modeling Research Group of the Hungarian Academy of Sciences at the Budapest University of Technology and Economics. They are also members of the Hungarian Academy of Sciences and the Academia Europaea (London).